2020
DOI: 10.3390/pharmaceutics12030203
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Evaluations of Catechin Hydrate Polymeric Nanoparticles Used in Brain Targeting for the Treatment of Epilepsy

Abstract: To formulate novel chitosan (CS)-coated–PLGA–nanoparticles (NPs) using a central composite design approach and use them in order to improve brain bioavailability for catechin hydrate (CH) through direct nose-to-central nervous system (CNS) delivery for the evaluation of a comparative biodistribution study of CH by the newly developed ultra high performance liquid chromatography mass spectroscopy and mass spectroscopy (UHPLC-MS/MS) method in the treatment of epilepsy. For PLGA–NPs’ preparation, a double emulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…The results demonstrated a higher amount of drug permeated to the brain when the nanoparticles were coated with the polymer. Furthermore, mucoadhesion at nasal mucosa suggested a high permanence of the nanosystem, with a release profile longer than 48 h [20][21][22]. Similar findings were observed with polymeric nanoparticles administered via intranasal to treat conditions such as cerebral ischemia (PLC nanoparticles) [23,24], for nociceptive pain (PLA (poly-lactide acid) nanoparticles) [90], or to transport neuroprotective molecules such as coenzyme Q10, or contrast agents (PLGA nanoparticles).…”
Section: Chitosan-decorated Nanoparticles For Brain Targetingsupporting
confidence: 60%
See 1 more Smart Citation
“…The results demonstrated a higher amount of drug permeated to the brain when the nanoparticles were coated with the polymer. Furthermore, mucoadhesion at nasal mucosa suggested a high permanence of the nanosystem, with a release profile longer than 48 h [20][21][22]. Similar findings were observed with polymeric nanoparticles administered via intranasal to treat conditions such as cerebral ischemia (PLC nanoparticles) [23,24], for nociceptive pain (PLA (poly-lactide acid) nanoparticles) [90], or to transport neuroprotective molecules such as coenzyme Q10, or contrast agents (PLGA nanoparticles).…”
Section: Chitosan-decorated Nanoparticles For Brain Targetingsupporting
confidence: 60%
“…Chitosan is a polymer natural widely utilized in different applications and approved for human use; it is a biodegradable, biocompatible, non-toxic, non-allergenic, and low-priced biomaterial; thus, chitosan is a suitable material for medical purposes [15]. Numerous studies have evaluated chitosan-coated nanosystems for the transportation of therapeutic compounds for the potential treatment of Alzheimer´s disease, Parkinson's disease, gliomas, cerebral ischemia, and schizophrenia [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro release of CTH from the CTH-PLGA-NPs & CS-PLGA-NPs were carried out in two separate release-medium with pH 7.40 and pH 5.50 in order to initiate the physiologic and acidic condition of cancer cells with slight modification ( Ahmad et al, 2018a , Ahmad et al, 2019 , Ahmad et al, 2020b ). Equal quantities of CTH-PLGA NP samples were packed in a dialysis sac and suspended in a 25.0 ml of the respective release medium having different pH 5.50 and pH 7.40.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…1.0 ml every test sample was withdrawn from each sampling-time point. After the withdrawal of every test sample, it was filtered through 0.20 μm syringe-filter and then analysed by UHPLC–MS/MS-method ( Ahmad et al, 2018a , Ahmad et al, 2019 , Ahmad et al, 2020b ).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…CH-coated PLGA and PCL nanoparticles for intranasal Rasagiline (RGN) [104], cathechin hydrate (CAT) [105] and glycyrrhizic acid (GA) [106] release were proposed for the treatment of various brain disorders. In all studies, pharmacokinetic experiments conducted in Wistar rats showed a significant high bioavailability and C max over the intravenous treatment group, confirming the suitability of nanoparticulate system as targeted brain dosage forms of hydrophilic molecules with undesirable side effects and high-hepatic first-pass metabolism.…”
Section: Targeting By Administration Routementioning
confidence: 99%